Pengaruh Implementasi Enterprice Resource Planning (ERP) Terhadap Profitabilitas dan Nilai Perusahaan PT. Sumber Alfaria Trijaya Tbk. - Yusriani Lebang Somalinggi; Agustinus Mantong; Grace Sriati Mengga (Jurnal Penelitian Multidisiplin, 2023)
Yusriani Lebang Somalinggi (2023). This study aims to determine the influence of the implementation of Enterprise Resource Planning (ERP) on the profitability and corporate value of PT. Sumber Alfaria Trijaya Tbk and find out whether profitability affects the company value of PT. Sumber Alfaria Trijaya Tbk . The sample in this research is PT. Sumber Alfaria Trijaya Tbk which is listed on the Indonesia Stock Exchange with financial reports for 2020-2022. The data analysis technique used was descriptive statistical test, multiple linear regression analysis, hypothesis testing and moderation test with the SPSS version 23 statistical calculator. The results showed that partially ERP implementation has a significant effect on profitability, ERP implementation also has a significant effect on firm value and profitability also has a significant effect on firm value. ERP implementation variables, profitability and firm value show values that have a close relationship between variables. So it can be concluded that ERP implementation has an effect on profitability and firm value at PT. Sumber Alfaria Trijaya Tbk.